PENGARUH MODEL QUANTUM LEARNING DISERTAI SPEED TEST TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 1 VII KOTO SUNGAI SARIAK - Maria Para Siska (STKIP Pesisir Selatan, 2021)
The purpose of this research to know the effect of Quantum Learning disertai Speed Test toward result of students mathematic at the seven Grade of SMPN 1 VII Koto Sungai Sariak. This research is pre-experimental study with research design randomized control group only design. The population in this research is the students of class VII SMPN 1 VII Koto Sungai Sariak. Sampling using random sampling technique with class VII7 as experiment class and VII6 as control class. The result of this research is the result of cognitive. Based on the final test, the mean score of experimental class was 74 and the control class was 67. The result of t- test tcalculate was 2.29 and ttable was 1.66 with a=0,05 and dk=54. Therefore tcalculate > ttable means H0 denied and H1 accepted. So, it was concluded that there is an influence of the Quantum Learning with Speed Test toward the result of students’ mathematic at the seven grade of SMPN 1 VII koto Sungai Sariak.